Improved Optimization of the Charge Simulation Method for the Calculation of the Electric Field Around Overhead Transmission Lines Using Statistical Methods - Allal, A.; Boubakeur, A.; Mujezinović, A. (Engineering, Technology & Applied Science Research, 2022)
In order to decide the appropriate arrangements of fictitious charges in the charge simulation method, the use of the Monte Carlo method is proposed for the estimation of the probability density function of two variables, the radius ratio, and the angle ratio. Τhe scale and shape parameters of the Weibull’s distribution are determined by the maximum likelihood estimator. The obtained results are used to calculate the electric field at arbitrary points in the neighborhood of high voltage transmission lines. The comparisons between the results computed by this method, the results calculated by the genetic algorithm, and those measured, confirm the effectiveness and accuracy of the proposed method.